Association between Using Rapid Dengue Tests and Treatment Outcomes and Effectiveness of Dengue Control in the Villages - Hanshaoworakul, Wanna; Wangteeraprasert, Tanaphon; Tasak, Sarayut; Phookaoluan, Jutikarn; Boon-in, Patcharin (Journal of Health Science of Thailand, 2017)
Dengue is a public health problem in Thailand and South East Asia region. Clinical manifestation varies from mild as no symptoms infection to severe as shock. It is believed that early and accurate diagnosis will result to better treatment outcome as well as effective control measure in the community. The outcome of using dengue rapid tests in Thailand is unclear. This study aimed to describe the magnitude of using rapid dengue test (RDT), and compared the outcome of treatment and the occurrence of secondary case in the same village between the cases that used and not used rapid dengue test for diagnosis. The study was begun by sending letters to both public and private hospitals in Thailand to obtain permission for conduct the study and determine the burden of dengue and dengue RDT utilization during 2013-2014 in those hospitals. We selected a hospital where there was high numbers of dengue cases with mixed of using and not using RDT for diagnosis. We reviewed medical record, investigation reports, and disease notification data base to collect data of clinical and case management, testing for dengue, time of disease report and control and secondary case in the villages. We defined a secondary case as a dengue patient reported in the surveillance system whose onset was within 16-35 days since the onset of the reviewed case. We entered and analyzed the data by EPI-info7. The Ethic Committee for Research in Human Subject, Department of Disease Control approved the study protocol. As for the results, we got 20.4 % response from 505 questionnaires sent to hospitals. We found that 50.5 % of respondents reported using RDT in their hospitals. The ratio of RDT utilization per dengue case diagnosed in private hospitals was higher than that of the public hospitals. The median of this ratio was 1.0 test per case (0-41.1) in 2013, and 3.0 test per case (0.3-41.3) in 2014. We reviewed 59 cases using RDT and 60 cases not using the RDT. The doctors correctly requested to test NS1 antigen within 1-9 days. We found that the mean length of stay for treatment among patients whom used the RDT was 3.4 + 1.7 days compared to 2.4 + 1.4 days whom not used RDT. We found no fatal cases in both groups and two cases in non- RDT group needed platelet replacement. The chance of having secondary case in RDT group was 1.9 times higher than the non- RDT group (relative risk = 1.9, 95% CI = 1.3 - 2.7). In conclusion, RDT was widely used for dengue diagnosis in hospitals. The longer length of stay in patients using RDT was possibly a result of early diagnosis and the concern of care givers. The higher risk of having secondary cases among patients used RDT suggested that control measures of dengue were not adequate to encounter the transmission despite the early diagnosis by RDT. The Department of Disease Control should identify more efficient criteria for using DRT and develop a national guideline for implementing the use of the test.